Approximation of ( ψ, β )-differentiable functions defined on the real axis by Weierstrass operators - Kalchuk, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Asymptotic equalities are obtained for upper bounds of approximations by the Weierstrass operators on the functional classes C^ψ_β, ∞ and L^ψ_β, 1 in metrics of the spaces C and L_1, respectively.